Imatinib Mesylate Reduces Neurotrophic Factors and pERK and pAKT Expression in Urinary Bladder of Female Mice With Cyclophosphamide-Induced Cystitis - Perkins, Megan; Girard, Beatrice M.; Campbell, Susan E.; Hennig, Grant W.; Vizzard, Margaret A. (Frontiers in Systems Neuroscience, 2022)
Imatinib mesylate is a tyrosine kinase inhibitor that inhibits platelet-derived growth factor receptor (PDGFR) -α, -β, stem cell factor receptor (c-KIT), and BCR-ABL. PDGFRα is expressed in a subset of interstitial cells in the lamina propria (LP) and detrusor muscle of the urinary bladder. PDGFRα+ interstitial cells may contribute to bladder dysfunction conditions such as interstitial cystitis/bladder pain syndrome (IC/BPS) or overactive bladder (OAB). We have previously demonstrated that imatinib prevention via oral gavage or treatment via intravesical infusion improves urinary bladder function in mice with acute (4 hour, h) cyclophosphamide (CYP)-induced cystitis. Here, we investigate potential underlying mechanisms mediating the bladder functional improvement by imatinib using a prevention or treatment experimental design. Using qRT-PCR and ELISAs, we examined inflammatory mediators (NGF, VEGF, BDNF, CCL2, IL-6) previously shown to affect bladder function in CYP-induced cystitis. We also examined the distribution of phosphorylated (p) ERK and pAKT expression in the LP with immunohistochemistry. Imatinib prevention significantly (0.05 ≤ p ≤ 0.0001) reduced expression for all mediators examined except NGF, whereas imatinib treatment was without effect. Imatinib prevention and treatment significantly (0.05 ≤ p ≤ 0.0001) reduced pERK and pAKT expression in the upper LP (U. LP) and deeper LP (D. LP) in female mice with 4 h CYP-induced cystitis. Although we have previously demonstrated that imatinib prevention or treatment improves bladder function in mice with cystitis, the current studies suggest that reductions in inflammatory mediators contribute to prevention benefits of imatinib but not the treatment benefits of imatinib. Differential effects of imatinib prevention or treatment on inflammatory mediators may be influenced by the route and frequency of imatinib administration and may also suggest other mechanisms (e.g., changes in transepithelial resistance of the urothelium) through which imatinib may affect urinary bladder function following CYP-induced cystitis.